2022
DOI: 10.3390/molecules27041247
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Cell Spheroids on Mixed Organic–Inorganic Superhydrophobic Coating

Abstract: Three-dimensional cell culture has become a reliable method for reproducing in vitro cellular growth in more realistic physiological conditions. The surface hydrophobicity strongly influences the promotion of cell aggregate formation. In particular, for spheroid formation, highly water-repellent coatings seem to be required for the significant effects of the process. In this work, surfaces at different wettability have been compared to observe their influence on the growth and promotion of aggregates of repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…As reported by the present authors, 3D spheroids have recently been promoted on surfaces of differing wettability, from hydrophilic to superhydrophobic [ 15 , 16 ]. Furthermore, both tumoral and non-tumoral cell lines have been grown on the prepared substrates in view of possible discrimination.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…As reported by the present authors, 3D spheroids have recently been promoted on surfaces of differing wettability, from hydrophilic to superhydrophobic [ 15 , 16 ]. Furthermore, both tumoral and non-tumoral cell lines have been grown on the prepared substrates in view of possible discrimination.…”
Section: Introductionmentioning
confidence: 78%
“…Almost all the applied methods are colorimetric assays as indirect methods for determining viable cells [ 15 ]. Previous studies have demonstrated the homogeneous distribution of viable cells in superhydrophobic-induced spheroids [ 16 ] using the acridine orange/ethidium bromide (AO/EB) double staining. In this work, however, the recovered 3D spheroids were grown in conventional 2D (monolayer) conditions as a measure of cell viability and migration of the cells forming cell aggregates ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2D cell culture, hydrophilic substrates promote cell adhesion and proliferation 59,86 , with moderate hydrophilicity yielding often the best cell response 61,62 . Conversely, in 3D cell culture, specifically for spheroid formation, high hydrophobic substrates induce the formation of spheroid-like cell aggregates at a higher degree of sphericity, as shown by Ferrari et al 60 and Lee et al 87 among others [88][89][90] . Zan et al 52 investigated the behaviors of three chondrogenic cell lines on PDMS substrates with different grades of hydrophilicity (WCA: 38.5°-120.4) and different stiffness (elastic modulus: 3.6-214.9 MPa).…”
Section: Hydrophilicitymentioning
confidence: 96%
“…Similarly, non-porous membranes deflected by gas pressure have been employed to compress or stretch cells in cartilage 32 , heart 33 , and bone-on-chip 34 models. It is known that cells react to environmental cues, thus all the physical properties of the membrane such as roughness [35][36][37][38][39][40] , surface microstructure [41][42][43][44][45][46][47] , mechanical strength [48][49][50][51][52][53][54][55][56][57][58] , hydrophilicity 35,36,52,[59][60][61][62] , and porosity 55,[63][64][65] have a significant effect on cellular adhesion and membrane biocompatibility. Despite their importance, these aspects are often neglected in OOC in which membranes are typically obtained from commercial Transwell inserts [66][67][68][69][70][71][72][73][74]…”
Section: Membrane-based Organs-on-chipmentioning
confidence: 99%